Uncultured Desulfobacteraceae and Crenarchaeotal group C3 incorporate 13C‐acetate in coastal marine sediment. Issue 4 (18th June 2015) - Na, Hyunsoo; Lever, Mark Alexander; Kjeldsen, Kasper Urup; Schulz, Frederik; Jørgensen, Bo Barker
Summary Stable isotope probing (SIP) of deoxyribonucleic acid (DNA) was used to identify microbes incorporating 13C‐labeled acetate in sulfate‐reducing sediment from Aarhus Bay, Denmark. Sediment was incubated in medium containing 10 mM sulfate and different 13C‐acetate (10, 1, 0.1 mM) concentrations. The resultant changes in microbial community composition were monitored in total and SIP‐fractionated DNA during long‐term incubations. Chemical analyses demonstrated metabolic activity in all sediment slurries, with sulfate‐reducing activity largely determined by initial acetate concentrations. Sequencing of 16S rRNA gene PCR amplicons showed that the incubations shifted the bacterial but not the archaeal community composition. After 3 months of incubation, only sediment slurries incubated with 10 mM 13C‐acetate showed detectable 13C‐DNA labeling. Based on 16S rRNA and dsrB gene PCR amplicon sequencing, the 13C‐labeled DNA pool was dominated by a single type of sulfate reducer representing a novel genus in the family Desulfobacteraceae. In addition, members of the uncultivated Crenarchaeotal group C3 were enriched in the 13C‐labeled DNA. Our results were reproducible across biological replicate experiments and provide new information about the identities of uncultured acetate‐consuming bacteria and archaea in marine sediments.